The Effect of Online Game Addiction on Sleep Quality in Adolescents Class VIII MTs Ma'arif Kaliwiro, Wonosobo - Kholifah Nur Azzakiyah; Pramesti Dewi; Asmat Burhan (Al-Makki Publisher, 2023)
Sleep quality is very beneficial for the human body, but sometimes it is hampered by bad activities such as playing online games that will make you addicted. Addiction to online games will make health disturbed. Teenagers who are addicted to online games have decreased physical strength due to a lack of physical movement and lack of sleep. This study aims to determine the effect of online game addiction on sleep quality in class VIII students of MTS Ma'arif Kaliwiro, Wonosobo. This type of research is a quantitative observational method using a cross-sectional approach and using a total sampling of 38 students of class VIII MTS Ma'arif Kaliwiro, Wonosobo. The results of the Spearman Rank test obtained a p-value of 0.000, which means p-value <0.05, which means that online game addiction influences sleep quality in class VIII adolescents at MTS Ma'arif Kaliwiro, Wonosobo with a correlation coefficient of 0.638. which means the strength of the relationship is strong. It is hoped that the results of this study can increase respondents' understanding of the importance of managing time to play online games so that sleep quality can be maintained properly.